Evaluación de la fertilidad de Suelos y Calidad de aguas, en el agroecosistema de la Granja San Pablo, Provincia De Los Ríos - Mora Calero, Fausto Alfonso (2019)
ABSTRACT The soils maps consist on the graphic representation of a certain area of the terrestrial surface, in those that appear reflected on a paper the different types of separate floors for their contours. In the case of the necessary floors non single era to classify them and to contain them the results obtained in the investigations to generalize, but evaluating them for their agricultural use, to know which the best option in use of each soil is or of an atmosphere (I am accustomed to more climate) and the evaluation of lands arises this way. Their main utility is to provide to those responsible for planning and handling (at different levels) the bases for the taking of more rational decisions. The work was carried out in the lands of the experimental farm "San Pablo", located in Km 7,5 of the road Babahoyo-Montalvo. The nutritional characteristics of the soils of the farm were investigated in function of their physical and chemical properties. Also the one was evaluated it contended of matter organic, potential hydrogen, floor texture and the sumatoria of interchangeable bases in lots of sampling of 1 m2; and in calicata of 2 m3 meters. Regarding the watering water they were carried out two samplings in river and in well, studying their physical quality and chemistry. The results show high levels of elements that can cause toxicity to the cultivations (Fe, Mn, Cu, Ca) and even very low of boron. The soil on the average is silty clay loam and it belongs to the group of the entisols. Keywords: Texture, characteristic, nutritious, bases, sampling.